Sistem Ketenagakerjaan di Indonesia dalam Perspektif Hukum Islam - Ali Fakhrudin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The purpose of this study is to analyze how the employment system in Indonesia is from the perspective of Islamic law. This research uses a socio-legal research approach, or empirical research (sociological juridical) which is oriented towards formal and substantial findings on the study of the labor system in Indonesia from the perspective of Islamic law. This approach is a combination of legal and social methods. Data analysis was carried out after examining and evaluating the data to determine its validity. After that, the data is grouped into categories or issues/themes according to the research objectives. As for the results of this study that in Islam, work is not only a personal relationship, workers or laborers with employers or entrepreneurs. Melain building social relations between humans in meeting the needs of family life, the surrounding community and as well as the ideal form of self-dedication of a servant to Allah Subhanahu Wata'ala. Therefore, there are four (4) principles in working in an Islamic perspective including; 1) independence, 2) nobility, 3) justice, and 4) clarity. Keywords: Employment System; Islamic law.